Factors of suicide-related behaviors based on stress-vulnerability model and prevention strategies among nurses: a scoping review - Yang, Xiaoyu; Hu, Deying; Li, Lecheng; Rezak, Rezvanguli (Frontiers in Psychology, 2025)
ObjectiveThe objective of this scoping review was to explore, appraise and synthesize the current literature regarding the incidence, factors influencing, and prevention strategies related to suicide risk among nurses.MethodsAn extensive literature search was conducted using databases such as PubMed, Web of Science, Medline, and Embase from its formation to June 20, 2024, specifically focusing on the suicide-related behaviors of nurses written in Chinese or English. Two researchers independently screened the literature, and disagreements were debated until a consensus was reached. Data extraction was conducted for the studies that were included. The process of data synthesis was carried out using narrative analysis.ResultsThe study encompassed 40 papers from 15 different countries. This study found that nurses’ suicide ideation ranged from 4.3 to 44.58%, while suicide attempts ranged from 2.9 to 12.6%. Based on the stress-vulnerability model, factors influencing nurses’ suicide-related behaviors include vulnerability (personality traits, coping styles), stressors (mental disorders, workplace bullying, etc.) and protective factors (social support, resilience, etc.). The strategies for preventing nurse suicide encompass primary prevention (for all nurses), secondary prevention (for nurses at risk of suicide), and tertiary prevention (for nurses who have attempted suicide).ConclusionThe suicide rate among nurses exceeds that of the general population. Mental disorders and workplace bullying are significant stressors that contribute to nurse suicide. Suicide-related behaviors among nurses can be effectively prevented and managed through the implementation of the tertiary prevention strategies. Primary prevention is essential in reducing suicide. Cognitive exercises and schedule shifts reasonably are primary preventive measures tailored for nurses. This study addresses the gaps in influencing factors about suicide-related behaviors among nurses and the strategies for preventing suicide, and provides a complete review of the current situation of nurses’ suicide-related behaviors, providing references for the safe management of nurses’ suicide.